Reproductive attributes of Hampshire, Gunghroo, Large Black and Tenyi Vo (local Naga Pig) under intensive management system in subtropical condition of Nagaland - SINGH, MAHAK; MOLLIER, R TALLIMOA; SHARMA, ROMEN (The Indian Journal of Animal Sciences, 2020)
Different reproductive attributes, viz. age at puberty, age at first mating, age at farrowing, litter size at farrowing, litter size at weaning, gestation period, weaning to estrus interval (WEI) and pre-weaning mortality were comparatively analysed in different breeds under intensive management system. Age at puberty, age at first mating and age at farrowing was significantly lower in Tenyi Vo pig compared to others breeds. Mean age of puberty varied from 185 days to 284 days. Age at first mating was recorded from 226 days in local Naga pig to 323 days in Hampshire. Age at first mating and age at first farrowing was significantly higher in Hampshire and Gunghroo breed as compared to Large Black and Tenyi Vo. Mean litter size at farrowing and weaning varied from 5 to 12 and 5 to 10, respectively. Litter size at farrowing and weaning was significantly higher in Large Black pig as compared to other breeds. Mean gestation period varied from 112 days in Gunghroo to 116 days in Tenyi Vo breed which differ significantly (P<0.05). WEI was significantly higher in Large Black compared to other breeds. Pre-weaning mortality was highest in Tenyi Vo breed (32%) and lowest in Hampshire breed (13%). In the present study, reproductive performance of Large Black, Gunghroo and Hampshire breed was recorded to be superior to Tenyi Vo pig. Also, reproductive performance of Large Black was better than other breeds.